Structural and Electrical Properties of Glass-Ceramic Ferroelectric Composite Materials - A. V. Tumarkin; E. N. Sapego; A. G. Gagarin; N. G. Tyurnina; Z. G. Tyurnina; O. Yu. Sinelshchikova; S. I. Sviridov (Известия высших учебных заведений России: Радиоэлектроника, 2022)
Introduction. Materials exhibiting high dielectric permittivity are relevant for use in modern ultrahigh-frequency electronics. Among them, ferroelectrics with high dielectric nonlinearity present particular interest. The electrical strength of ferroelectric materials can be increased using modern composite structures based on mixing ferroelectries and linear dielectrics - materials exhibiting simultaneously low dielectric permittivity and high electrical strength. This approach provides for the opportunity of creating new multicomponent materials with previously unattainable properties and adjusting their component composition, inclusion size and electrical properties across a wide range. In this work, on the basis of porous potassium-iron-silicate glass (KFS) obtained by ion exchange, glass-ceramic materials containing barium titanate were synthesized for use at ultrahigh frequencies.Aim. Production of glass composites by low-temperature sintering of pre-synthesized BaTiO3 (BTO) and potassium-iron-silicate glass, as well as characterization of their structural and electrical properties at ultrahigh frequencies (microwave).Materials and methods. The crystal structure and phase composition of the obtained films were studied by X-ray diffraction using a DRON-6 diffractometer by the emission spectral line CuKα1 (λ = 1.5406 Å). The dielectric permittivity (ε) of microwave samples was evaluated by the Nicholson-Ross method at room temperature using an Agilent E4980A LCR-meter.Results. According to X-ray diffraction analysis, the synthesized samples are a mixture of KFS glass, ferroelectric BaTiO3 and dielectric barium polytitanates; the ratio of the latter determines the electrical properties of the composites. Depending on the content of barium titanate, the studied samples demonstrate a dielectric constant from 50 to 270 at a dielectric loss level of 0.1...0.02. The samples subjected to annealing in an oxygen medium showed an increase in dielectric permittivity by 10.25 % and an increase in controllability with a decrease in dielectric losses by an average of two times.Conclusion. The composite composition of 70 wt % BTO /30 wt % KFS was found to be the most promising in terms of structural and electrical properties. This composite showed an increase in dielectric permittivity by 25 % and a significant increase in nonlinearity, at the same time as reducing losses by more than two times as a result of annealing in an oxygen medium.